Instead of dying: poems - Haldeman, Lauren, author; The Center for Literary Publishing, Colorado State University, publisher (Colorado State University. Libraries, 2017)
Invoking spiders and senators, physicists and aliens, Lauren Haldeman's second book, Instead of Dying, decodes the world of death with a powerful mix of humor, epiphany, and agonizing grief. In the spirit of Calvino's Invisible Cities, these poems compulsively imagine alternate realities for a lost sibling ("Instead of dying, they inject you with sunlight & you live" or "Instead of dying, you join a dog-sledding team in Quebec"), relentlessly recording the unlived possibilities that blossom from the purgative magical thinking of mourning. Whether she is channeling Google Maps Street View to visit a scene of murder ("Because / a picture of this place is / also a picture of you"), or investigating the origins of consciousness ("Yes, alien / life-forms exist / they are your thoughts"), Haldeman wrenches verse into new sublime forms, attempting to both translate the human experience as well as encrypt it, inviting readers into realms where we hover, plunge, rise again, and ascend.--Provided by publisher.
Keywords: Death -- Poetry; Grief -- Poetry